A Influence Digital Marketing And Brand Awerness To Decision Purchase Ultrajaya UHT Milk at Minimarket X in Bandung City - joni; Novi Rukhviyanti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Digital transformation has changed the marketing strategies of the fast-food consumer goods industry, particularly UHT milk, which faces intense competition in the Indonesian market. This study aims to analyze the influence of digital marketing and brand awareness on purchasing decisions for Ultrajaya UHT milk at Minimarket X in Bandung City. Methods research using approach quantitative explanatory with A survey technique was used to select 95 consumer respondents through purposive sampling. The research instrument was a structured questionnaire with a Likert scale that had been tested for validity and reliability. Data analysis used multiple linear regression with the help of SPSS software version 29. Results Partial tests show that Digital Marketing has a significant positive effect on purchasing decisions, as does Brand Awareness. show influence positive significant to Decision purchase. The simultaneous test results showed that both variables had a significant effect together, explaining 62.5 percent of the variation in purchasing decisions. This finding confirms that integrating digital marketing strategies and strengthening brand awareness are crucial factors in improving consumer purchasing decisions in the UHT milk industry in the digital era.